Communication Channels and Innovative Farmer Behaviour in South Croatia - Natalija Ćurčin; Želimir Dulčić; Slaana Pavlinović Mršić (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
The aim of this paper is to explore the innovation practices and communication chanels used by farmers in south Croatia. Namely, this area is characterised by a very sensitive karstic environment, and rural and agricultural abandonment. Given conditions call for introduction of agricultural practices which will reconcile requirements to protect this unique landscape and at the same time make local farmers living more attractive. In order to understand which are the factors that can reverse the trends, this paper studies farmer decision-making and behaviour with respect to innovations in agriculture with a particular emphasis on communication chanels that farmers use to obtain necessary information. Namely, innovations in agriculture may positively affect farmer competitiveness and in this way contribute to regeneration of rural areas. However, lack of relevant information and subsequent uncertainty about outcome of innovative behavior may discourage farmers to introduce new practices. In order to reduce mentioned information asymmetry further knowledge on communication chanels is needed. For this reason, this paper explores attributes and attitudes of local farmers with respect to their experience and decision-making about agricultural innovations, as well as communication chanels which are affecting their behavior. Results of a pilot survey conducted on convenient sample of farmers from Split-Dalmatia and Dubrovnik-Neretva counties are discussed. Insights about innovative behaviour obstacles and advantages provide further improvement directions for the competitiveness of local farmers in vulnerable rural areas.
Keywords: 650; Communication channels; Agriculture; Attitudes; Competitiveness